A murine model of acute and prolonged abdominal sepsis, supported by intensive care, reveals time-dependent metabolic alterations in the heart - Bart Jacobs; Inge Derese; Sarah Derde; Sarah Vander Perre; Lies Pauwels; Greet Van den Berghe; Jan Gunst; Lies Langouche (Intensive Care Medicine Experimental)
Abstract Background Sepsis-induced cardiomyopathy (SICM) often occurs in the acute phase of sepsis and is associated with increased mortality due to cardiac dysfunction. The pathogenesis remains poorly understood, and no specific treatments are available. Although SICM is considered reversible, emerging evidence suggests potential long-term sequelae. We hypothesized that metabolic and inflammatory cardiac changes, previously observed in acute sepsis as potential drivers of SICM, partially persist in prolonged sepsis. Methods In 24-week-old C57BL/6J mice, sepsis was induced by cecal ligation and puncture, followed by intravenous fluid resuscitation, subcutaneous analgesics and antibiotics, and, in the prolonged phase, by parenteral nutrition. Mice were killed after 5 days of sepsis (prolonged sepsis, n = 15). For comparison, we included acutely septic mice killed at 30 h (acute sepsis, n = 15) and healthy controls animals (HC, n = 15). Cardiac tissue was collected for assessment of inflammatory and metabolic markers through gene expression, metabolomic analysis and histological assessment. Results In prolonged sepsis, cardiac expression of IL-1β and IL-6 and macrophage infiltration remained upregulated (p ≤ 0.05). In contrast, tissue levels of Krebs cycle intermediates and adenosine phosphates were normal, whereas NADPH levels were low in prolonged sepsis (p ≤ 0.05). Gene expression of fatty acid transporters and of the glucose transporter Slc2a1 was upregulated in prolonged sepsis (p ≤ 0.01). Lipid staining and glycogen content were elevated in prolonged sepsis together with increased gene expression of enzymes responsible for lipogenesis and glycogen synthesis (p ≤ 0.05). Intermediate glycolytic metabolites (hexose-phosphates, GADP, DHAP) were elevated (p ≤ 0.05), but gene expression of several enzymes for glycolysis and mitochondrial oxidation of pyruvate, fatty-acyl-CoA and ketone bodies to acetyl-CoA were suppressed in prolonged sepsis (p ≤ 0.05). Key metabolic transcription factors PPARα and PGC-1α were downregulated in acute, but upregulated in prolonged, sepsis (p ≤ 0.05 for both). Ketone body concentrations were normal but ketolytic enzymes remained suppressed (p ≤ 0.05). Amino acid metabolism showed mild, mixed changes. Conclusions Our results suggest myocardial lipid and glycogen accumulation and suppressed mitochondrial oxidation, with a functionally intact Krebs cycle, in the prolonged phase of sepsis, together with ongoing myocardial inflammation. Whether these alterations have functional consequences and predispose to long-term sequelae of SICM needs further research.